2004
DOI: 10.1007/s00467-003-1397-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and cardiovascular involvement in children with neurofibromatosis type1

Abstract: We evaluated blood pressure in a sample of patients with neurofibromatosis type 1 (NF1), using ambulatory blood pressure monitoring (ABPM), to determine whether ABPM, when compared with casual BP recordings, allowed the detection of a higher risk for hypertension. We also evaluated the correlation between BP and vascular abnormalities. We studied 69 NF1 patients (36 males and 33 females) with a mean age of 11+/-4 years, divided into group A, with 24-h mean systolic blood pressure (SBP) or diastolic blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…[8] Many reports in the literature have shown cardiac involvement in NF1, including valvular pulmonary stenosis, branch peripheral pulmonary stenosis, atrial and ventricular septal defects, coarctation of the aorta (thoracic and abdominal), and hypertrophic cardiomyopathy. [3,[9][10][11] In a recent study, Lin et al [10] reported that the prevalence rate of cardiovascular abnormalities in patients with NF1 is low (2.3%). However, in another study, Lama et al [11] described cardiac abnormalities in 13 of 69 patients (18.8%) with NF1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8] Many reports in the literature have shown cardiac involvement in NF1, including valvular pulmonary stenosis, branch peripheral pulmonary stenosis, atrial and ventricular septal defects, coarctation of the aorta (thoracic and abdominal), and hypertrophic cardiomyopathy. [3,[9][10][11] In a recent study, Lin et al [10] reported that the prevalence rate of cardiovascular abnormalities in patients with NF1 is low (2.3%). However, in another study, Lama et al [11] described cardiac abnormalities in 13 of 69 patients (18.8%) with NF1.…”
Section: Discussionmentioning
confidence: 99%
“…[3,[9][10][11] In a recent study, Lin et al [10] reported that the prevalence rate of cardiovascular abnormalities in patients with NF1 is low (2.3%). However, in another study, Lama et al [11] described cardiac abnormalities in 13 of 69 patients (18.8%) with NF1. They found 4 patients with cardiac heart disease, 2 patients with mild mitral regurgitation, 2 patients with mild aortic regurgitation, 2 patients with hypertrophic cardiomyopathy, and 1 patient with mitral valve prolapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our literature review found six cohorts from seven articles that considered the prevalence of pre-hypertension and hypertension in patients with NF-1; 7.4–22% and 6.1–23.4% for pre-hypertension and hypertension, respectively ( 16 22 ). In five of the studies ( 16 20 , 22 ), the patients were children and young adults (1.5–25 years) with a high prevalence of early-onset hypertension, suggesting the necessity of regular blood pressure monitor in young patients with NF-1, and the patients in the study conducted by Zinnamosca et al ( 21 ) were middle-aged adults. Dubov et al ( 19 ) found the lowest prevalence of hypertension (6.1%) by measuring office blood pressure of 114 patients with NF-1, whereas Tedesco et al ( 17 ) found the highest prevalence (23.4%) using the same method and criteria in a different cohort of 64 patients with NF-1.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, clinical manifestations include learning disabilitiesand an increased risk of malignancy [13]. Hypertension and precocious puberty (PP) are frequent complications in NF occurring in approximately 16% [4,5] and 2,5–5% [68] respectively. More than a half of hypertensive NF1 patients do not have one of the two well-known causes either renal artery stenosis or pheochromocytoma [9].…”
Section: Introductionmentioning
confidence: 99%